Evolving radiation oncology techniques in the 21st century: the FLASH technique - Pellizzon, Antonio Cassio Assis (Brazilian Journal of Oncology, 2020)
Radiation therapy (RT) uses high doses of high energy X-rays to kill cancer cells. Fractionation and volume optimization were the main methods used to increase the dose given to the tumor and reduce the dose and side effects to the normal tissues (NT). Conventional RT works with dose rates up to 0.1 Gy per second. Opportunities to improve the biological efficacy of RT have been explored and options involving dose rate modulation are now available. Preclinical studies showed a drastic reduction in NT toxicity with preserved antitumor efficacy when using FLASH RT, furthermore this method enables higher doses to be given to the tumor. We reviewed the principles of FLASH RT.
Keywords: Toxicity; Radiation dosage; Free radicals; Oxidation-reduction; Adverse effects